Answer:
The value of x for the given expression is
Explanation:
Given as :
The expression is written
3
- 1
× x = 1
Or, 1
× x = 3
- 1
Or,
× x =
- 1
Or,
× x =
- 1
Or,
× x =
![(7-2)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2j66oninlqrsisvczza7exdq24wrpya74h.png)
Or,
× x =
![(5)/(2)](https://img.qammunity.org/2020/formulas/mathematics/college/2q1j3h0vc6dybtf2k79ot9scqho9y4uz62.png)
∴ x =
![((5)/(2))/((4)/(3))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1gotjhwkjxa30xc9xijphsyih7mpzucykb.png)
Or, x =
![(5* 3)/(2* 4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q82tszrtup2m4q2ngvpd9h658a5iy94sw0.png)
I.e x =
![(15)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dawdj5wk9piqws92i05u0thpspxmojrdp0.png)
So, The value of x =
![(15)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dawdj5wk9piqws92i05u0thpspxmojrdp0.png)
Hence The value of x for the given expression is
Answer